A comparison of microsatellites and genome‐wide SNPs for the detection of admixture brings the first molecular evidence for hybridization between Mustela eversmanii and M. putorius (Mustelidae, Carnivora). (23rd August 2021) - Szatmári, Lajos; Cserkész, Tamás; Laczkó, Levente; Lanszki, József; Pertoldi, Cino; Abramov, Alexei V.; Elmeros, Morten; Ottlecz, Barnabás; Hegyeli, Zsolt; Sramkó, Gábor
Abstract: Introgressive hybridization can pose a serious threat to endangered species which have an overlapping distribution such as in the case of two polecat species, Mustela eversmanii and M. putorius, in Europe. The population size of steppe polecat is known to continuously shrink, whereas its sister species, the European polecat, is still somehow widespread. In this study, we perform an analysis using microsatellite (SSR) and genomic (SNP) data sets to identify natural hybrids between polecats. Four populations were genotyped for eight polymorphic SSR loci, and thousands of unlinked SNPs were generated using a reduced‐representation sequencing approach, RADseq, to characterize the genetic make‐up of allopatric populations and to identify hybrids in the sympatric area. We applied standard population genetic analyses to characterize the populations based on their SSR allelic frequency. Only a single sample out of 48 sympatric samples showed exact intermediacy that we identified as an F1 hybrid. Additionally, one specimen was indicated in the genomic data sets as backcrossed. Other backcrosses, indicated by SSRs, were not validated by SNPs, which highlights the higher efficacy of the genomic method to identify backcrossed individuals. The low frequency of hybridization suggests that the difference in habitat preference of the two species may act as a barrier to admixture. Therefore, it is apparently unlikely that polecat populations are threatened by significant introgression. The two species showed a clear genetic differentiation using both techniques. We found higher genetic diversity values in the sympatric steppe polecat population than in the other studies on polecat populations. Although M. putorius is a hunted species in most countries, genetic diversity values indicate worse conditions in Europe than in the protected sibling species M. eversmanii . Suspending hunting and providing protected status of the former seems to be reasonable and timely.